Patterns and Determinant Factors Of Arabica Coffee’s Marketing Margin In Ngada Regency - Maria Clara Mau; Dwidjono Hadi Darwanto; Masyhuri Masyhuri Masyhuri (Agro Ekonomi, 2018)
Coffee is one of the essential plantation commodities in the development process of plantation sub-sector. Ngada Regency is one of the coffee producers in East Nusa Tenggara Province. Coffee in Ngada Regency becomes one of the plantation commodities that conceive high potential to be developed. This research aims to discover the established marketing channel pattern, factors  influencing marketing margin of Arabica coffee, and the quantity of price received by farmers the in Ngada Regency. The respondents in this research were 59 farmers who were derived randomly and 10 merchants who were derived from snowball sampling technique. This research used  interview with a questionnaire as supporting tools in collecting the data. This research analyzed the data descriptively and multiple regression analysis was also conducted through Ordinary Least Square method. The analysis results show that (1) the established marketing channel pattern of Arabica coffee in Ngada Regency are channel I: Farmers - Product Processing Unit – PT. Indocom (sold in the form of red logs coffee that is processed into Hard Skin coffee), channel II: Farmers – PT. Indocom (sold in the form of Hard Skin coffee) and channel III: Farmers – Collected Traders – Retailers – Consumer (sold in the form of coffee beans). (2) The factors that influence the marketing margin are marketing volume and marketing cost. The distance and coffee processing do not have any significant influence towards the marketing margin. (3) The marketing channel that conceives high value of farmer’s share is the marketing channel II.